An executive order in a modern English presidential discourse - Yesypenko, Nadia (Гельветика, 2021)
The major objectives of this study are to investigate and analyze Donald Trump’s forty-four executive orders signed in 2019 from the point of structure and functions of institutional documents in American political discourse, in which we can grasp the effective and dominant principles of directives of the president of the United States which are issued in the exercise of president’s powers in the executive branch of the government. The most comprehensive categorization of presidential documents was found in the archive of the Jacob Burns Law Library since each type of documents is distinguished as a separate unit: executive agreements, messages to Congress, statements of administration policy, executive orders, proclamations, state of the Union Address, determinations, reorganization plans, directives, speeches, signing statements, letters, presidential commission reports and memoranda. Critical Discourse Analysis frameworks based on a structural and pragmatic approaches are used to depict a rigid structure of executive orders and their purpose to provide guidelines for different agencies of the executive branch of the US government, on the one hand, and to interpret various policies aimed at a larger audience. The results represent that there are obligatory sections in the executive orders (date of their issue, title, introduction, sections with their purpose and policy, main body sections, general provisions section, the president’s signature, indication “The White House”, one more reference to the date of their issue and a billing code), though minor variations are possible to indicate responsible authorities, ways of establishment or functions of newly-formed commissions, termination and revocation of previously-issued executive orders. Executive orders have distinct functions. They are generally aimed at guiding the government and agencies of the USA. The study shows, they do not affect the interests of private individuals. Although executive orders are addressed to the federal government, they can regulate a wide range of debatable issues of public interest, such as the implementation of international treaties, public procurement, access to the state information, issues of war and peace, sanctions for trade with individual countries or the constitutional foundations of an American society.
Keywords: political discourse; discourse analysis; presidential discourse; text structure; pragmatic function; executive order